Analisis Rasio Keuangan Dalam Menilai Kinerja Keuangan Pada PT. Royal Prima,Tbk Yang Terdaftar Di Bursa Efek Indonesia (BEI) 2021-2024 - Fista Lindu Aprilia; Marshanda; Sherly Indah Kania; Fitri Yani Panggabean (CV. ITTC INDONESIA, 2025)
This study uses financial ratio analysis including liquidity, solvency, and profitability ratios to evaluate the financial performance of PT Royal Prima Tbk. from 2021 to 2024. Descriptive quantitative methodology with a comparative analysis approach against industry norms was used. Information was obtained from the company's annual financial statements, which are available on the official website of the Indonesia Stock Exchange. The findings show that the company's liquidity ratio is still erratic and is below the industry standard. The solvency ratio shows a fairly healthy capital structure, but the increase in liabilities in the last year without being followed by net profit growth has the potential to pose a financial risk. On the other hand, profitability ratios such as ROA, ROE, and NPM have decreased, which reflects the non-optimal utilization of assets and equity to generate profits. Overall, the financial performance of PT Royal Prima Tbk during the period is considered not optimal and requires strategic efforts in cost efficiency and increased productivity to achieve business sustainability.